El uso táctico de las armas de fuego en las guerras civiles peruanas (1538-1547) - Espino López, Antonio (2012)
During the civil wars between the conquistadores, Peru was a field of experimentation for the new military tactics developed in Europe following the introduction of portable infantry firearms. This article suggests that, however, the techniques introduced by Francisco de Carvajal, Gonzalo Pizarro’s fieldmaster, predated those used in Europe by several decades, especially regarding the rate of fire in combat. In the battle of Huarina (1547), Carvajal used his own method to ensure his infantry’s ability to deliver heavy fire. The technique relied on adequate training and on the number of weapons each soldier carriedin battle, rather than on the number of men.